Evaluating The Cumulative Line Spread Function For ZnSe Infrared Material In The Optical Design of Lenses - Mohamad, A. R.A.S.; Abass, R. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The present research aims to study the efficiency of infrared material lenses compared with the glass material lenses by determining LSF and CLSF for perfect optical system having circular aperture, Arnorphous(1,2) material transmitting infrared radiation (AMTIR) is used for infrared window, lenses and prisms when transmission in the range of 1-14 pm is desired in application like thermal imaging, astronomical and forward looking infrared (FLIR), AMTIR is the low thermal change in refractive index 72 * 10-6 /C Â° is an advantage in lenses design to prevent defocussing.